Hubungan Tingkat Pendidikan, Pengetahuan, Usia dan Riwayat Keluarga DM dengan Perilaku Pencegahan Diabetes Mellitus Tipe 2 pada Usia Dewasa Muda - Amalia Ayu Ramadhani; Roissiana Khotami (Yayasan Literasi Sains Indonesia, 2023)
Diabetes Mellitus is one of the diseases that need to be lookout into since its prevalence is continuously increasing. Approximately 98% of the total Diabetes Mellitus cases are type 2 diabetes mellitus. The prevalence number nearly increases significantly at the age of 45 and above. Hence, it is crucial to take preventive action at an earlier age. East Java is one of the 5 provinces with the highest diabetes mellitus prevalence. The city with the highest diabetes mellitus prevalence is Madiun which reached 5.33% prevalence. Diabetes mellitus prevalence in the Taman district is also increasing every year. This research aims to understand the relationship between educational level, knowledge, age, and family health history with diabetes mellitus and the preventive action of type 2 diabetes mellitus in young adult age in Taman district, Madiun. This research used a quantitative method with a cross-sectional research design. The sample was 110 respondents aged 20-40, residing in Taman district, Madiun. This research also used a random sampling technique. The independent variables were educational level, knowledge, age, and family health history with diabetes mellitus, while the dependent variable was the preventive action of type 2 diabetes mellitus. The data were then analyzed by using a chi-square statistical test. This research shows there was no significant relationship between educational level, knowledge, and age to the preventive action of type 2 diabetes mellitus (p-value > 0.05). However, there is a significant relationship between family health history with diabetes mellitus to the preventive action of type 2 diabetes mellitus (p-value < 0.05).